La conectividad y su incidencia en la gestión por procesos del hospital Dr. Juan Montalván Cornejo, en el cantón Urdaneta, Provincia de los Ríos, año 2013, propuesta alternativa. - Martillo Pinto, Agustín Bolívar (2015)
This research study conducted at the Hospital Juan Cornejo Montalvan, Ricaurte Parish, Canton Urdaneta, Los Ríos province, aims to demonstrate the inadequate service to external users in the nursing home due to manual handling of medical records, long columns of waits to access medical specialists shifts, lack of information on in-hospital procedures, weak training of personnel who have direct patient contact, etc. This research seeks to establish the relationship between connectivity and its impact on the management process in Juan Montalván Hospital, as it is evident that there is in this health unit limited technological infrastructure which affects the quality of services and the new management model in public institutions leads to work with Information Technology and Communications (ICT). And to overcome the problems in this nursing home a joint effort between the public health authorities of the Canton Urdaneta and the developer of this research is proposed. Which significantly contribute to implement an efficient Management by Process that is consistent with the requirements of government policies through Connectivity. The information and communications technologies have become nowadays a fundamental axis around which revolve all the sciences of the world; the proposed solution for Dr. Juan Cornejo Montalván Hospital focuses on implementing a converged network services including voice, data and video on a single network structured parking. Convergent Network Services for HJMC including data, voice and video. It will allow all network traffic flows through the same network; The introduction of modern technology in this nursing home will be a significant advance in public hospitals in the province of Los Rios and costs associated with the implementation of the proposal it is $ 29,952.80 which the authorities must manage the Zonal Coordination Health 5